(untitled) (Kathmandu University Medical Journal, 2014)
Morbus Osler-Weber-Rendu syndrome also known as Hereditary hemorrhagic telangiectasia (HHT) and Meckel’s diverticulum is a rare combination disorder. Our case presented with the recurrent obscure gastrointestinal (GI) bleeding for several years. He came with a massive active lower gastrointestinal bleeding. Ultimatively, he underwent an exploratory laparotomy along with intraoperative colonoscopy. A Meckel’s diverticulum in combination with multiple erosions was found as a probable cause of the massive gastrointestinal bleeding. An ileo-caeacal resection had been performed and by the pathologist multiple telangiectasias in the resected ileum were established. Blood was sent for genetics and was negative for ENG, ALK-1, and SMAD-4 genes. The patient was discharged after 10 days from time of admission and is under regular follow up without any further bleeding. In this case, despite sophisticated techniques for investigations the cause of the GI-bleeding with several esophagogastroduodenoscopies and colonoscopies, mesenteric angiography and finally an oral double balloon enteroscopy was misdiagnosed till the intra operative endoscopy showed a middle GI-bleeding. The management for obscure GI-bleeding is discussed for countries with lower medical facilities like Nepal in our case with Morbus Osler-Weber-Rendu syndrome. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11034 Kathmandu University Medical Journal Vol.11(1) 2013: 81-85